2018
DOI: 10.1111/ijsa.12197
|View full text |Cite
|
Sign up to set email alerts
|

Construct‐based approach to developing a short, personality‐based measure of integrity

Abstract: Covert integrity measures are thought to draw from the Big Five dimensions of conscientiousness, agreeableness, and emotional stability. Using a construct‐based approach, we had subject matter experts identify items from a Big Five personality measure, the Trait Self‐Descriptive Personality Inventory that reflected an operational definition of integrity. The resulting 10 items exhibited a three‐factor structure that corresponded to the three Big five dimensions associated with integrity. Study 1 used primary (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 65 publications
0
7
0
1
Order By: Relevance
“…Stab.—“Factor Alpha” or “Stability”—than a 6th factor on same level’. In a similar way, Catano, O'Keefe, Francis, and Owens (, p. 90) speculated as to whether Honesty‐Humility ‘is a sixth personality factor … or simply a second‐order factor based on three of the Big Five dimensions’.…”
Section: Summary Of Objections To Adoption Of Hexaco Model and Responmentioning
confidence: 95%
“…Stab.—“Factor Alpha” or “Stability”—than a 6th factor on same level’. In a similar way, Catano, O'Keefe, Francis, and Owens (, p. 90) speculated as to whether Honesty‐Humility ‘is a sixth personality factor … or simply a second‐order factor based on three of the Big Five dimensions’.…”
Section: Summary Of Objections To Adoption Of Hexaco Model and Responmentioning
confidence: 95%
“…The importance of integrity and self-discipline is not surprising as both are facets of conscientiousness, and previous research has consistently shown a relatively strong correlation of conscientiousness with job performance. However, integrity is rarely considered as a unique facet (it is not included as a facet in the FFM) and is sometimes considered a composite of factors (Catano, O'Keefe, Francis, & Owens, 2018) or a behavior to be measured with an integrity test (Schmidt & Hunter, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Integrity. We used a personality-based measure of integrity developed by Catano et al (2018). This measure conceptualizes integrity as a second-order personality construct comprised of agreeable, conscientiousness, and emotional stability.…”
Section: Cognitive Reflection Testmentioning
confidence: 99%